Psychological Symptoms and Well-Being After Treatment for Primary Aldosteronism - Velema, Marieke S.; Terlouw, Jannie M.; de Nooijer, Aline H.; Nijkamp, Marjan D.; Jacobs, Nele; Deinum, Jaap (Hormone and Metabolic Research, 2018)
Primary aldosteronism (PA) is an increasingly identified cause of secondary hypertension. PA can be caused by an aldosterone-producing adenoma or by bilateral adrenal hyperplasia, generally treated by adrenalectomy or mineralocorticoid receptor antagonists, respectively. Recent studies suggest that PA is associated with more psychological symptoms and lower levels of well-being. The purpose of this study was to investigate the associations between subtype of PA and psychological symptoms and well-being after specific treatment. We analyzed the outcomes of the Mental Health Continuum-Short Form and the Symptom Checklist in 160 patients (mean age 57 years; 74.3% males) with PA, comparing the scores for psychological symptoms and well-being between both subtypes of PA. Additionally, we performed subgroup analyses based on gender, age, time since initiation of treatment, and co-morbidity. Moreover, we compared the results with published norm scores. Mean follow-up after adrenalectomy or start of medication was four years and two months. Depressive symptoms, anxiety and obsessive-compulsive thoughts and well-being did not differ between subtypes of PA. Subgroup analysis did not reveal any differences, except for women with bilateral adrenal hyperplasia who scored higher on the anxiety subscale than women after adrenalectomy. Compared to the general population, patients with treated PA reported more psychological symptoms. In contrast, well-being did not differ significantly from norm scores. Subtype and treatment of PA were no important determinants of psychological symptoms and well-being on the long-term. We suggest that physicians should be alert for psychological symptoms, as these were more frequently present in patients with PA.
Keywords: hyperaldosteronism; patient-reported outcome; psychopathology; life satisfaction